Effects of key leadership determinants on business sustainability in entrepreneurial enterprises - Suparak Suriyankietkaew (2022)
Purpose: Today’s small enterprises are forced to rethink their business-as-usual management and shift toward corporate sustainability. The empirical paper responds to a crucial quest for many modern leaders and entrepreneurs, specifically small business owners in emerging economies. This paper aims to answer what they can do to increase long-term financial performance and enhance stakeholder satisfaction, thereby contributing to long-term business sustainability. Design/methodology/approach: Using a convenience sampling, data were collected from a sample of 280 business leaders and entrepreneurs of small enterprises across industries in an emerging economy of Thailand. This study used a sustainable leadership research framework. Factor analysis and multiple regression analysis were used for data analysis. Findings: Seven valid and reliable leadership factors were uncovered as new underlying leadership constructs to examine business sustainability in small entrepreneurial enterprises in Thailand. Results from multiple regressions revealed two significantly positive factors or drivers (i.e. trusting, innovative team orientation and strong, shared vision) for enhanced two sustainability performance outcomes (i.e. financial performance and stakeholder satisfaction). The findings thus contribute to advance our limited knowledge about the contextualised constructs and possible theoretical development of the developing research realm. Research limitations/implications: Successful small entrepreneurial organisations in Thailand and other emerging economies that wish to improve their business sustainability are suggested to adopt the essential leadership and management practices (i.e. trusting, innovative team and strong, shared vision). Future studies may examine data from a larger sample size and other countries to expand our limited understanding in different contexts. Practical implications: The resulting practical insights can be used to guide business leaders, entrepreneurs, practitioners and policymakers towards making strategic priorities and investments for improved business competitiveness, resilience and sustainability in small entrepreneurial enterprises. Overall, this study may be a starting point for further investigation on developing entrepreneurial growth and business sustainability in small sustainable enterprises across emerging economies. Originality/value: The paper responds to calls for more contextualised research studies in the evolving multidisciplinary field of entrepreneurial leadership and business sustainability, particularly in an emerging economy of Thailand. It also unveils the essential strategic leadership factors that positively drive business sustainability in small entrepreneurial firms. And, it empirically examines the effects of diverse strategic leadership factors and multiple sustainability performance outcomes in a single study. It further proposes an emergent leadership-performance model for entrepreneurial business sustainability in the context-specific study. Above all, it advances the currently limited empirical knowledge in the emerging research front towards more sustainable futures.